Some constraints on the modeling using the uranium isotopes U-238 and U-234 for dating groundwaters from Guarany aquifer, South America - Bonotto, Daniel Marcos [UNESP] (Wit Press, 2000)
Groundwaters from the Guarany aquifer located at the South American continent and sampled at four wells with described geological sections in São Paulo State, Brazil, were chemically and isotopically analysed with two aims: to evaluate the quality of this important hydrological resource and to investigate the possibility of using the natural uranium isotopes U-234 and U-238 as a chronological tool, since the U-234/U-238 activity ratio and dissolved U content data in groundwater systems have generated models for dating purposes.